Faktor-Faktor yang Mempengaruhi Psychological Well Being Ibu Hamil dan Ibu Menyusui Saat Masa Pandemi COVID-19 di Surabaya - Fauziah Fitri Hernanto; Nurul Ramadhani Yaner; Roby Aji Permana (2022)
COVID-19 has become a global health emergency and has a complex impact on every aspect of people's lives. One of the vulnerable groups is pregnant women and breastfeeding mothers. Psychological well-being needs to be achieved by pregnant women and breastfeeding mothers to be able to get through conditions of uncertainty and threats during the pandemic. The purpose of this study was to analyze the factors that affect psychological well being in pregnant women and breastfeeding mothers during the COVID-19 in Surabaya. This research was an analytic correlational study with a cross sectional approach. The population of this study were all pregnant women and mothers who were breastfeeding with babies aged less than 6 months at the time of data collection, domiciled or resided in Surabaya. The sampling technique in this study was simple random sampling with a total sample of 198 respondents consisting of 130 pregnant women and 68 breastfeeding mothers. The results of the spearman rho test showed that income, history of pregnancy/birth history, history of COVID-19, and family support had an effect on the psychological well being of pregnant and lactating women. The COVID-19 history variable has the largest coefficient value which indicates that this variable has a strong influence on the psychological well being of pregnant women and breastfeeding mothers during the COVID-19 in Surabaya.